Ion‐exchange adsorption of calcium ions from water and geothermal water with modified zeolite A. Issue 2 (21st November 2014) - Song, Junchao; Liu, Mingyan; Zhang, Yang
<x xml:space="preserve">Abstract</x> The modified zeolite A was prepared by a two‐step crystallization method to remove scale‐forming cations from water and geothermal water. The adsorption kinetics, mechanism and thermodynamics were studied. The calcium ion adsorption capacity of the modified zeolite A was 129.3 mg/g (1 mg/g = 10−3 kg/kg) at 298 K. The adsorption rate was fitted well with pseudo‐second‐order rate model. The adsorption process was controlled by film diffusion at the calcium ion concentration less than 250 mg/L (1 mg/L = 10−3 kg/m3), and it was controlled by intraparticle diffusion at the concentration larger than 250 mg/L. The calculated mass‐transfer coefficient ranged from 2.23 × 10−5 to 2.80 × 10−4cm/s (1 cm/s = 10−2m/s). Dubinin–Astakhov isotherm model could appropriately describe the adsorption thermodynamic properties when combined with Langmuir model. The adsorption process included not only ion exchange but also complexation between calcium and hydroxyl ions. The adsorption was spontaneous and endothermal. The high adsorption capacity indicates that the modified zeolite A is a suitable adsorption material for scale removal from aqueous solution. © 2014 American Institute of Chemical Engineers AIChE J, 61: 640–654, 2015